2018
DOI: 10.1002/biof.1473
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in HIV‐infected patients: Cross site‐specific hydrolysis of H1 histone and myelin basic protein

Abstract: Histones act as damage‐associated molecules, while anti‐DNA antibodies are directed against histone‐DNA nucleosomal complexes. Myelin basic protein (MBP) plays an important role in the pathogenesis of multiple sclerosis. Autoantibodies (Abs) with enzymatic activities are the distinctive feature of some autoimmune and viral diseases. Abzymes with proteolytic activity against different proteins specifically hydrolyze only these specific proteins. Using chromatography of IgGs on columns with immobilized H1 histon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
120
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(127 citation statements)
references
References 52 publications
(174 reference statements)
1
120
0
Order By: Relevance
“…Molecular mimicry and the consequent potential cross-reactivity following infections have been repeatedly described in humans. [1][2][3][4][5][6][7][8][9][10][11][12] Such cross-reactivity is not evident in experimental infections of primates. 13 Actually, following preclinical studies performed in primates [14][15][16][17][18] as recommended by the Food and Drug Administration, 19 the reports declare that primate active immunization by pathogen vaccine administration is well tolerated and exempt of relevant events.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular mimicry and the consequent potential cross-reactivity following infections have been repeatedly described in humans. [1][2][3][4][5][6][7][8][9][10][11][12] Such cross-reactivity is not evident in experimental infections of primates. 13 Actually, following preclinical studies performed in primates [14][15][16][17][18] as recommended by the Food and Drug Administration, 19 the reports declare that primate active immunization by pathogen vaccine administration is well tolerated and exempt of relevant events.…”
Section: Introductionmentioning
confidence: 99%
“…The literature describes the widespread phenomenon of cross-complexing certain antibodies and enzymes with foreign ligands-antigens [ 32 , 33 , 34 , 46 ]. At the same time, cross-catalysis in the case of canonical enzymes is an extremely rare occurrence [ 47 ]. It was shown that abzymes against any specific protein usually hydrolyze only this, but no other control proteins [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that abzymes against any specific protein usually hydrolyze only this, but no other control proteins [ 30 , 31 , 32 , 33 , 34 ]. The first examples of cross-catalytic activity of antibodies have been discovered recently [ 41 , 47 ]. It has been shown that IgG antibodies against human histones effectively hydrolyze myelin basic protein (MBP) and, conversely, antibodies against MBP cleave histones [ 41 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations